Kidney transplantation with positive complement-dependent lymphocytotoxicity crossmatch with negative flow crossmatching and Luminexx donor-specific antibodies. (August 2013) - Kute, Vivek B.; Vanikar, Aruna V.; Gumber, Manoj R.; Trivedi, Varsha B.; Shah, Pankaj R.; Patel, Himanshu V.; Balwani, Manish R.; Modi, Pranjal R.; Trivedi, Hargovind L.
Abstract The presence of positive anti-human, globulin-enhanced, complement-dependent cytotoxicity crossmatches (AHG-CDC-XM) generally has been considered as a contraindication to kidney transplantation (KTx). Flow cytometry crossmatch (FCXM) and solid phase antibody screening are most sensitive and specific methods for immunological assessment. The outcome effect of donor-specific antibody (DSA) positive by Luminexx platform and CDCXM negative has been evaluated, but not the outcome of CDCXM positive and DSA negative. This is a case report describing KTx in a patient with pre-transplant positive AHG-CDC-XM but negative FCXM and without detectable DSA by Luminexx single antigen beads. CDCXM, FCXM, DSA were negative after transplantation, and kidney allograft biopsy did not show immune injury with negative C4d. Our report suggests that KTx with positive AHG-CDC-XM can be considered if FCXM and DSA were negative with careful immunological monitoring after transplantation. In our case, the IgM-antibodies were responsible for the positive AHG-CDC-XM result. The patient with positive CDC XM has a good outcome in the absence of DSA. Further work is needed to determine under what circumstances CDCXM positive transplants can be performed with FCXM and DSA negative.